Transitiontopractice guidelines: Enhancing the quality of nursing education - T Bvumbwe; N Mtshali (South African Medical Association, 2018)
Background. A de-link between initial training and transition to practice has been reported. Effective transitioning to practice enhances competences and confidence among newly graduated nurses.Objectives. To develop transition-to-practice guidelines as a tool to complement efforts to improve nursing education in Malawi.Methods. A multi-method design was used within the framework of the Stufflebeam context, input, process, product (CIPP) model. Analysis of reports from a nursing conference derived four core concepts, highlighting the context within which goals for transition-to-practice guidelines needed to be focused on. A panel discussion suggested guidelines based on these concepts. Review meetings and a review of the literature, local policies and standards were conducted to provide input to enhance credibility and reproducibility of the proposed guidelines. Consensus workshops involving nurse educators, nursing clinical preceptors, nurse practitioners and policymakers were conducted as a process evaluation for the guidelines.Results. Four core concepts emerged from the process of guideline development. Eleven guideline statements were formulated as a product of the guideline development process. Although newly graduated nurses are exposed to various clinical settings during college training, nurses’ skills and clinical judgement are still rather weak and need more formal support. The guidelines provide assistance for transition to practice among newly graduated nurses.Conclusion. Nursing education is a complex process that starts at student recruitment and should effectively progress until transition to practice. Transition-to-practice guidelines to complement other guidelines in nursing education are timely in Malawi.